About influence of effects nonequilibrity and nonlocality on the parameters of the discharge sustained by surface waves - Azarenkov, N.A.; Gushchin, Vl.V.; Gushchin, V.V. (Вопросы атомной науки и техники, 2003)
The kinetic equation for plasma in two-dimensional non-uniform field of a surface wave was obtained. At the approximation of predetermined field there were found the distribution functions in dependence on the value of a coefficient of spatial attenuation. With using such distribution functions such plasma characteristics as density, frequency of elementary processes, diffusion coefficients, number of particles falling down to the wall, were calculated. There was shown that in high frequency electric field transport may also have anisotropic character. Taking this into account the “correct” hydrodynamic equations were obtained. Comparison with earlier known results was carried out. As result of this work it is possible to state – taking into account the non-equilibrium and nonlocal properties is important for description of discharges sustained with surface waves. Отримано кінетичне рівняння для плазми у двомірнонеоднорідному полі поверхневої хвилі. У наближенні сталого поля знайдено вирази для функцій розподілу у залежності від величини коефіцієнту просторового послаблення. За допомогою цих функцій розподілу підраховано такі характеристики плазми, як густина плазми, частоти елементарних процесів, коефіцієнти дифузії, кількість частинок, що потрапляють на стінки. Наведено, що у високочастотному електричному полі перенос також може носити анізотропний характер. З урахуванням цього отримано „вірні” гідродинамічні рівняння. Проведено порівняльний характер з раніше відомими результатами. Як підсумок роботи можливо стверджувати, що урахування нерівноважності та не локальності важливо, якщо описувати розряди, що підтримуються поверхневими хвилями. Получено кинетическое уравнение для плазмы в двумернонеоднородном поле поверхностной волны. В приближении заданного поля найдены выражения для функций распределения в зависимости от величины коэффициента пространственного ослабления. С помощью этих функций распределения посчитаны такие характеристики плазмы как плотность, частоты элементарных процессов, коэффициенты диффузии, количество частиц, попадающих на стенки. Показано, что в высокочастотном электрическом поле перенос тоже может носить анизотропный характер. С учетом этого получены «правильные» гидродинамические уравнения. Проведен сравнительный анализ с ранее известными результатами. Как итог работы можно утверждать – учет неравновесности и нелокальности важен при описании разрядов, поддерживаемых поверхностными волнами.